Impact of 5G/6G Networks on the Development of IOT, Robotics, and Autonomous Systems. Low Latest and Mass Connection of Devices - Taran, A.; Sotnik, S. (NURE, 2026)
The work analyzes the impact of fifth- and sixth-generation telecommunications networks on the development of Internet of Things systems, robotics, and autonomous platforms. It examines the key technical characteristics of 5G and 6G networks, including data transfer speed, signal latency, and device connection density. A comparative analysis of the capabilities of different mobile network generations was conducted, and specific technological solutions for critical system classes were identified. It has been established that the transition to next-generation networks eliminates the fundamental limitations of traditional telecommunications technologies and creates an infrastructural foundation for the widespread implementation of real-time, autonomous systems. У роботі проаналізовано вплив телекомунікаційних мереж п'ятого та шостого поколінь на розвиток систем Інтернету речей, робототехніки та автономних платформ. Досліджено ключові технічні характеристики мереж 5G та 6G, зокрема швидкість передачі даних, затримку сигналу та щільність підключень пристроїв. Проведено порівняльний аналіз можливостей різних поколінь мобільних мереж та визначено специфічні технологічні рішення для критичних класів систем. Встановлено, що перехід до мереж нового покоління усуває фундаментальні обмеження традиційних телекомунікаційних технологій та створює інфраструктурну основу для масового впровадження автономних систем реального часу.
Вплив 5G/6G мереж на розвиток IoT, робототехніки та автономних систем. Низькі затримки та масове підключення пристроїв
Keywords: 5G; 6G; Internet of Things; robotics; autonomous systems; Інтернет речей; робототехніка; автономні системи